Combination of 5% Dextrose Ringer's solution and egg yolk extender maintained the motility and viability of kampung rooster spermatozoa in chilled temperature - Ahmad Hanif Azzam; Dadik Rahardjo; Tatik Hernawati; Sri Pantja Madyawati; Budi Utomo (Universitas Airlangga, 2022)
This study aims to determine the motility and viability of kampung rooster (Gallus domesticus) spermatozoa in 5% Dextrose Ringer's solution as an extender with or without the addition of various egg yolk concentrations at 5ºC during storage. Semen was collected by massage in the morning. In this study, four types of extenders were used, i.e., 5% Dextrose Ringer's extender without egg yolk, 5% Dextrose Ringer's extender with 5, 7.5, and 10% egg yolk for T0, T1, T2, and T3, respectively. Then, 1000 IU Penicillin and 1 mg Streptomycin were added per mL extender. Fresh semen from each rooster was evenly divided into four volumes to be diluted 11 times in each group extender. Extended semen from all groups was stored at 5°C. Data were analyzed using ANOVA and Duncan's new multiple range test. The result showed a significant difference (p <0.05) between each treatment group for spermatozoa motility and viability. In conclusion, this study revealed that the addition of various concentrations of egg yolk into 5% Dextrose Ringer's solution as an extender maintained the motility and viability of kampung rooster spermatozoa.